Design of Acceptance Decision Support System for New Employees in the Technician Position Using AHP and TOPSIS Methods at CV. Techindo Global Solution - dominic adello setiawan; Riki Riki; Yo Ceng Giap (Komunitas Dosen Indonesia, 2018)
An agency cannot be separated from the role of human resources (HR) working in it. The quality of human resources is one factor to improve the productivity of an institution's performance. Therefore, an assessment in employee selection is an important part of providing qualified employees for the company. Problems that occur in CV Techindo Global Solutions is the process of receiving employees who are still using the manual way and based on subjective assessment results so that the process of acceptance of employees to be slow and inaccurate. The absence of an application program in support of decision making for employee recruitment. Based on this, the author designed the decision support system of employee appraisal on CV. Techindo Global Solutions using AHP (Analytic Hierarchy Process) and TOPSIS (Technique For Order Preference by Similarity to Ideal Solution) methods. Employee acceptance system is done by using Analytic Hierarchy Process method to determine the weight of each criterion and the use of Technique For Order Performance by Similarity to Ideal Solution to conduct ranking alternatives in the form of employee data. This system is built with PHP and MySQL programming language as database. With the program using AHP and TOPSIS method, the new employee's assessment is better than the individual assessment and with the decision support information system, the process of receiving the employee can be helped from the evaluation side.